The Impact Of Using Gadget With Insomnia Cases At Teenagers In Semambung Village, Kanor Sub Districts, Bojonegoro Districts - Budi Purwaningtyas, Nadya Nenva Desy; Sodik, Muhammad Ali (Universitas STRADA Indonesia, 2021)
The high number of gadgets use among teenagers today causes many negative impacts for them. Things that have a negative impact are experienced by teenagers in using gadgets, because at this age they tend to have no maturity in recognizing their identity and environment, considering that adolescence has vulnerabilities in self-esteem and depression. The purpose of this study was to analyze the impact of using gadgets on the incidence of insomnia at teenagers in Semambung Village, Kanor Sub District, Bojonegoro District. The population in this study were all teenagers in Semambung Village, Kanor Sub District, Bojonegoro District as many as 215, the number of samples in this study was 143 respondents taken by purposive sampling technique. The instrument used in this study was a questionnaire. Data analysis used Spearman Rho Correlation statistical test and processed using SPSS 16 for windows. The results showed that the majority of respondents, namely 113 respondents (79%) used old gadgets, more than some of the respondents, namely 102 respondents (71.3%) experienced insomnia, based on the results of the SPSS test on the Rho Spearman correlation test with a significance value of 0.000 (0.000 < 0.05) concluded there is a relationship between the use of gadgets with the incidence of insomnia in teenagers. The intensity of using gadgets increases during the pandemic, because all learning is done online. So that teenagers inevitably have to interact longer with gadgets which ultimately increases the occurrence of insomnia.